2021
DOI: 10.1016/j.amsu.2021.102813
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the diagnostic accuracy of contrast-enhanced/DWI MRI and ultrasonography in the differentiation between benign and malignant myometrial tumors

Abstract: Background Various modalities including ultrasonography and magnetic resonance imaging (MRI) have been developed as imaging technique for screening malignant myometrial tumors, but a few studies assessed the diagnostic value of these two techniques in differentiation of benign from malignant myometrial tumors that had been the main purpose of this study. Materials and methods This cross-sectional study was performed on 63 women underwent surgery for intrauterine masses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…Najibi et al [ 28 ] compared the diagnostic accuracy of contrast-enhanced/DWI MRI and ultrasonography in the differentiation between benign and malignant myometrial tumors. The cross-sectional study observed 63 patients that underwent surgery for intrauterine masses and were assessed using the ultrasound and MRI.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Najibi et al [ 28 ] compared the diagnostic accuracy of contrast-enhanced/DWI MRI and ultrasonography in the differentiation between benign and malignant myometrial tumors. The cross-sectional study observed 63 patients that underwent surgery for intrauterine masses and were assessed using the ultrasound and MRI.…”
Section: Resultsmentioning
confidence: 99%
“…In a previously mentioned study, Najibi et al [ 28 ] compared the diagnostic accuracy of contrast-enhanced/DWI MRI and ultrasonography. In contrast to ultrasonography, with the MRI, the correct diagnosis was made in all but four cases, leading to a sensitivity of 94.6%, specificity of 92.3%, positive predictive value of 94.6%, negative predictive value of 92.3%, and accuracy of 93.7% for the MRI to detect sarcoma.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…American scientists [ 43 ] have achieved good performance in predicting mesenchymal malignant lesions in the uterus by applying a radiomics model of ultrasound images. Compared with ultrasonography, MRI has the advantages of good soft-tissue resolution and multidirectional and multiparametric imaging [ 44 ], which can more effectively differentiate uterine sarcomas from uterine fibroids; thus, when ultrasonography suggests the possibility of malignant uterine tumors, MRI should be continuously examined.…”
Section: Imaging Examinationsmentioning
confidence: 99%